Mandatory Application of Diniyah Madrasah (Basic Islamic Studies) at Formal Schools: Regional Government Policy Studies - Arif Wahyudi; Mohd Aderi Che Noh (ISTAWA, 2019)
The lack of Islamic Religious Education in Blitar Regency, this phenomenon has led to the innovation of Islamic Education in Blitar district through the application of the Mandatory Madrasa Diniyah (Madin) Program in all formal junior high, high school and vocational level institutions as intracurricular. The aim of the study was to examine how the application of Islamic Education innovations and to find out how the implementation of Islamic Education innovation through the Diniyah Madrasah Mandatory program in formal institutions applied in Blitar district. The results of the study show its application by means of the district's national education institutions together with the Madin Education and Development Institution giving debriefing to selected teachers to prepare Madin's learning in formal institutions. For the ninth grade students will get a Madin certificate as a graduation requirement as well as a requirement to proceed to the next level and form a teaching and learning activity Madin in a formal institution with a combination of placement test methods, peer tutor method (study group students who are coordinated by their own friends), and drill methods (how to learn by repeating the material many times).Minimnya Pendidikan Agama Islam di wilayah Kabupaten Blitar, fenomena ini memunculkan adanya inovasi Pendidikan Agama Islam di kabupaten Blitar melalui penerapan Program Wajib Madrasah Diniyah (Madin) diseluruh lembaga formal tingkat SMP, SMA, SMK sebagai intrakurikuler. Tujuan penelitian untuk mengkaji bagaimana penerapan inovasi Pendidikan Agama Islam dan untuk mengetahui bagaimana penerapan inovasi Pendidikan Agama Islam melalui program Wajib Madrasah Diniyah di lembaga formal yang diterapkan di kabupaten blitar. Hasil penelitian menunjukan penerapannya dengan cara lembaga pendidikan nasional kabupaten bersama dengan Lembaga Pendidikan dan Pengembangan Madin (LPP Madin) memberikan pembekalan kepada guru terpilih guna mempersiapkan pembelajaran Madin di lembaga formal. Bagi siswa-siswi kelas sembilan akan mendapatkan sertifikat Madin sebagai syarat kelulusan sekaligus sebagai persyaratan untuk melanjutkan ke jenjang berikutnya dan bentuk KBM (Kegiatan Belajar Mengajar) Madin di lembaga formal dengan kombinasi  metode Placement Test (Tes penempatan kemampuan), metode Tutor Sebaya (kelompok belajar siswa yang di koordinatori oleh temannya sendiri), dan metode Drill (cara belajar dengan  mengulang  materi sampai berkali-kali).